The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1365-2141.1998.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated TFPI in malignant disease: relation to cancer type and hypercoagulation

Abstract: Summary.We have previously reported high levels of the coagulation inhibitor TFPI in the blood of patients with gastrointestinal cancer. TFPI is not an acute-phase reactant, but high levels have also been reported in patients with septicaemia and disseminated intravascular coagulation (DIC). To study its relationship with other types of malignancy, TFPI activity was first determined in plasma samples from 214 patients with various malignancies. In a second cohort of 83 patients, total and free TFPI antigen, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 42 publications
(54 reference statements)
0
38
1
Order By: Relevance
“…Stimulation of the membrane glycoprotein LAMP2 suggests that this adhesive glycoprotein may promote tumor invasion and metastasis in hepatocarcinoma patients (Sarafian et al 1998). The tissue factor pathway inhibitor TFPI, which inhibits the extrinsic coagulation system, was activated in liver cancer patients and may reduce fibrin formation (Iversen et al 1998). Inactivation or repression of one or more of these products by drug intervention may slow the progression of hepatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the membrane glycoprotein LAMP2 suggests that this adhesive glycoprotein may promote tumor invasion and metastasis in hepatocarcinoma patients (Sarafian et al 1998). The tissue factor pathway inhibitor TFPI, which inhibits the extrinsic coagulation system, was activated in liver cancer patients and may reduce fibrin formation (Iversen et al 1998). Inactivation or repression of one or more of these products by drug intervention may slow the progression of hepatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It could be a consequence of the hypercoagulability in cancer patients, since thrombin induces a redistribution and acute release of TFPI in vitro as well as in vivo in animals [22, 23]. However, Iversen et al [24]failed to demonstrate any correlation between TFPI and the markers of activated coagulation in patients with solid tumors. For these authors the high TFPI levels would have a deleterious effect by inhibiting fibrin formation which is produced as a defense mechanism against tumor invasion.…”
Section: Changes In Inhibitor Levelsmentioning
confidence: 99%
“…Concentration of TFPI in plasma is increased in patients with acute myocardial infarction 21,22. There are also reports on increased plasma levels of TFPI in relation to diabetes mellitus,23 renal diseases,24 and cancer 25,26. Recently we demonstrated that exogenous addition or over-expression of heparanase by transfected cells resulted in release of TFPI from the cell surface and its accumulation in the cell culture medium 27.…”
Section: Heparanase Releases Cell Surface Tissue Factor Pathway Inhibmentioning
confidence: 97%
“…Importantly, the in vitro studies were supported by elevation of TFPI levels in the plasma of transgenic mice over-expressing heparanase. Moreover, increased levels of TFPI have been noted in the plasma of cancer patients,25,26 reflecting, possibly, induction of heparanase expression and elevation of its plasma levels revealed by ELISA assay 28. In human umbilical vein endothelial cell (HUVEC) and tumor-derived cell lines, release of TFPI from the cell surface correlated with enhanced TF-mediated coagulation.…”
Section: Heparanase Releases Cell Surface Tissue Factor Pathway Inhibmentioning
confidence: 99%